Protection mechanisms and services for young workers in Central Asia and the European Union - Kulakhmetova, Anel; Justus Liebig University Giessen (My University, 2010)
The UN Convention on the rights of the child speaks not only about needs but about the rights of children from the moment of a birth. The Convention covers a wide scale of the rights consolidated in three basic categories: - The right to life, - The right for survival and development, - The right for protection and participation. The Convention provisions assume that children should live in the environment providing for realization of their rights starting from the right for a name and citizenship and ending with the medical and sanitary care and education. They have the right to shelter from torture, exploitation, arbitrary detention, and unreasonable deprivation of family care. Children have the right to participate in decisions concerning their lives and to participate in the life of the local community.The Convention is not the hierarchy of the rights and therefore, one right cannot possible have a higher priority in comparison with the other right. The Convention demonstrates that all rights of the child are equally important. Rights complement each other and provide for survival and development of the child. The countries-signatories to the Convention make a commitment to respect and ensure the whole complex of rights stipulated by the Convention for each child within the limits of the state jurisdiction without any discrimination (UN CONVENTION ON THE RIGHTS OF THE CHILD 1989, ARTICLE 2(1)). The state and the family are responsible for guaranteeing, respecting, and realizing the rights of the child. It is widely accepted that the state has a central and a primarily beneficial role in the protection of young people. Therefore, even if children experience extreme abuse or are neglect from their families the state authorities are supposed to provide comfort to those children. In the field of childhood studies there has been plentiful debate about the role of the state in children´s lives. Less attention is given to the ways in which the state is a source of risk for children (BOYDEN 2007, P. 240). The present research tries to show that with an effort to limit the influx of illegal migrants to their own countries many governments fail to realize their obligations towards migrant children. In many cases for reasons of national security they try to limit the rights of the child, putting at stake a notion of childhood as a life phase free from political blemish: in legal terms at least, children are the bearers of rights that cannot be compromised or alienated by circumstance.There are 192 countries of the world ratified the UN Convention on the rights of the child, including five Central Asian states. (ALSTON/TOBIN 2005, P. 10) Having joined the UN CRC, Central Asian countries have undertaken a wide range of obligations requiring serious revision of the current legislation, of the corresponding mechanisms for coordination of the child protection system and monitoring of the rights´ implementation. However, the UN Committee on the rights of the child in the concluding observations to periodic reports provided by the countries marks that there are still a number of problems in this area: - In countries of Central Asia the national legislation does not always fully comply with principles of the UN Convention on the rights of the child; - Lack of necessary financial and human resources, lack of the comprehensive approach in the child protection hinders the work of coordinating structures involved in the child rights protection (UNICEF INNOCENTI RESEARCH CENTER 2006, P. 31). - Lack of the statistical data on children, first of all, about the most vulnerable groups of children, hinders monitoring of the Convention implementation. Due to these existing problems the issues of children especially in need of assistance fall out of the focus of the governments. These children become «invisible» which means that the rights of these children will not be satisfied even at the level of basic needs such as sufficient nutrition, health care, school education and family care. The reasons causing such situations are lack of the data about children in the state agency of statistics, lack of the records about these children during development of the state program, duplication of functions of various departments and ministries.In 2006, countries of Central Asian initiated the Forum on child protection to overcome these problems. Issues of social policy, protection and inclusion of children, creation of the social protection system and overcoming of fragmentation were discussed. The Forum has demonstrated that it is an effective instrument for interstate cooperation and exchange of experience. Hereafter, it can serve as an impulse to conduct the integrated Forums (Forum on education, Forum on maternity and child health, Forum on child protection). The regional analysis of child protection systems shows that there is a fragmentation of the current child care systems. There is a multitude of actors, not necessarily well coordinated that have to respond to complex family situations and different child protection problems. Reforms of current child care systems into a continuum of services that provide individualized responses, rather than collectivist responses is one of the important regional lessons learned to strengthen the current system response. There are many implications for governments in this work: - They must be driving the vision for change and articulate operational plans, guiding principles for the reform as well as targets for the coming years. - Governments also need to be active in enforcing what are the core responsibilities of the state. This includes setting standards for the operation for the system, carry out gate-keeping functions, accreditation, provide support to planning, costing and budgeting at regional and local levels, defining the minimum package of services; and development of targeted social policies to support most vulnerable families - To overcome fragmentation and ensure proper coordination of the work, governments are also responsible for bridging gaps between sectors, coordination and facilitating institutional and professional capacity development. This includes regulate allocation of resources (decentralization with equity), define obligations of the different sectors (including responsibilities of the professionals encompassed in job descriptions), ensure continuum of services between the different actors (includes identifying missing services and functions) and improve professional competencies (job descriptions, training, lessons learned, sharing potential good practices, etc.) - Finally, governments need to take full responsibility for review of quality of services provided through monitoring of services (beyond financial monitoring), development of methods for result-based management, support to systems for data collection, provide opportunities for competition in service provision between state actors and NGOs. Having signed the UN Convention on the rights of the child, the governments of all Central Asian countries have undertaken to respect the rights of children, including the right to the proper standard of living. The governments of Central Asia should be aware of necessity to input funds in development of children because children are the future. Since 1998, the region enjoyed economic growth while the economic recession was left behind. Taking the economic growth into the account as well as reduction of the birth rate, today all Central Asian countries have a unique chance to invest in education and public health for the future of their children. In the long-term prospect these investments will allow the younger generation to make their own investment.
Keywords: ddc:330